Scheduling With Alternatives Machine Using Fuzzy Inference System And Genetic Algorithm. - Kamaruddin, Shahrul; Mokhtar, Mohzani; Subari, Khairanum; Othman, Zalinda (Universiti Sains Malaysia, 2008)

(untitled)
As the manufacturing activities in today's industries are getting more and more complex, it is required for the manufacturing company to have a good shop floor production scheduling to plan and schedule their production orders.